Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Programs from Proofs of Predicated Dataflow Analyses - Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 30th Annual ACM Symposium on Applied Computing)
Programs from Proofs" is a generic method which generates new programs out of correctness proofs of given programs. The technique ensures that the new and given program are behaviorally equivalent and that the new program is easily verifiable, thus serving as an alternative to proof-carrying code concepts. So far, this generic method has one instantiation that verifies type-state properties of programs. In this paper, we present a whole range of new instantiations, all based on data ow analyses. More precisely, we show how an imprecise but fast data ow analysis can be enhanced with a predicate analysis as to yield a precise but expensive analysis. Out of the safety proofs of this analysis, we generate new programs, again behaviorally equivalent to the given ones, which are easily verifiable" in the sense that now the data ow analysis alone can yield precise results. An experimental evaluation practically supports our claim of easy verification.

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Verification and Simulation of Self-Adaptive Mechatronic Systems - Heinzemann, Christian

Optimizing Water Tanks in Water Distribution Systems by combining Network Reduction, Mathematical Optimization and Hydraulic Simulation - Hallmann, Corinna; Suhl, Leena (OR Spectrum)
In the last two decades, water consumption in Germany has been decreasing, which causes the water tanks and pipes in water distribution systems to work inefficiently. This paper proposes a method that supports the planning process for tanks in water distribution systems. The method uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a non-convex Mixed Integer Quadratically Constrained Program (MIQCP) that is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computing times, the size of the water distribution system model is reduced before building the optimization model. After applying several network reduction techniques and using a piecewise approximation of the original model, there may be some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water distribution system model, the solution is verified by a hydraulic simulation. If the solution is not feasible, the reduced model has to be modified and solved again until the hydraulic simulation verifies a solution as feasible. In this paper, each of these processes is described and the results indicate the usefulness of each of them.

Homodyne detection with on-off detector systems - Lipfert, T.; Sperling, Jan; Vogel, W. (Physical Review A)

Continuous sampling of the squeezed-state nonclassicality - Agudelo, E.; Sperling, Jan; Vogel, W.; Köhnke, S.; Mraz, M.; Hage, B. (Physical Review A)

Unified nonclassicality criteria - Ryl, S.; Sperling, Jan; Agudelo, E.; Mraz, M.; Köhnke, S.; Hage, B.; Vogel, W. (Physical Review A)

Convex ordering and quantification of quantumness - Sperling, Jan; Vogel, W (Physica Scripta)

Entanglement and phase properties of noisy NOON states - Bohmann, M.; Sperling, Jan; Vogel, W. (Physical Review A)

Entanglement witnesses for indistinguishable particles - Reusch, A.; Sperling, Jan; Vogel, W. (Physical Review A)

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Balanced homodyne detection with on-off detector systems: Observable nonclassicality criteria - Sperling, Jan; Vogel, W.; Agarwal, G. S. (EPL (Europhysics Letters))

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

An overview of the BIOASQ large-scale biomedical semantic indexing and question answering competition - Tsatsaronis, George; Balikas, Georgios; Malakasiotis, Prodromos; Partalas, Ioannis; Zschunke, Matthias; R. Alvers, Michael; Weissenborn, Dirk; Krithara, Anastasia; Petridis, Sergios; Polychronopoulos, Dimitris; Almirantis, Yannis; Pavlopoulos, John; et al. (BMC Bioinform.)

Linked SDMX Data: Path to high fidelity Statistical Linked Data - Capadisli, Sarven; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

Semantic Quran - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

SINA: Semantic interpretation of user queries for question answering on interlinked data - Shekarpour, Saeedeh; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille; Auer, Sören (J. Web Semant.)

DeFacto - Temporal and multilingual Deep Fact Validation - Gerber, Daniel; Esteves, Diego; Lehmann, Jens; Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Speck, René (J. Web Semant.)

Question Answering over Linked Data (QALD-5) - Unger, Christina; Forascu, Corina; López, Vanessa; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena; Cimiano, Philipp; Walter, Sebastian (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

HAWK@QALD5 - Trying to Answer Hybrid Questions with Various Simple Ranking Techniques - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

CETUS - A Baseline Approach to Type Extraction - Röder, Michael; Usbeck, Ricardo; Speck, René; Ngonga Ngomo, Axel-Cyrille (Semantic Web Evaluation Challenges - Second SemWebEval Challenge at ESWC 2015, Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ESWC Developers Workshop 2015 co-located with the 12th Extended Semantic Web Conference {(ESWC} 2015), Portorož, Slovenia, May 31, 2015)

Evaluating Entity Annotators Using GERBIL - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

HAWK - Hybrid Question Answering Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Bühmann, Lorenz; Unger, Christina (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

Automating RDF Dataset Transformation and Enrichment - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

LODFlow: a workflow management system for linked data processing - Rautenberg, Sandro; Ermilov, Ivan; Marx, Edgard; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

An optimization approach for load balancing in parallel link discovery - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

Motive-based Search - Avdiyenko, Liliya; Nettling, Martin; Lemke, Christiane; Wauer, Matthias; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (KDIR 2015 - Proceedings of the International Conference on Knowledge Discovery and Information Retrieval, part of the 7th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management {(IC3K} 2015), Volume 1, Lisbon, Portugal, November 12-14, 2015)

Using Caching for Local Link Discovery on Large Data Sets - M. Hassan, Mofeed; Speck, René; Ngonga Ngomo, Axel-Cyrille (Engineering the Web in the Big Data Era - 15th International Conference, ICWE 2015, Rotterdam, The Netherlands, June 23-26, 2015, Proceedings)

DeLFI 2015 - The 13th e-Learning Conference on Computer Science of the E-Learning Section of the Society for Computer Science eV - Pongratz, Hans; Keil, Reinhard

FEASIBLE: A Feature-Based SPARQL Benchmark Generation Framework - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

ASSESS - Automatic Self-Assessment Using Linked Data - Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

WebArena - R {\ "a} spacious structures for ü r the learning locations of the future - Winkelnkemper, Felix; Oberhoff, Andreas

An Open Question Answering Framework - Marx, Edgard; Soru, Tommaso; Esteves, Diego; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LSQ: The Linked SPARQL Queries Dataset - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

The LSQ Dataset: Querying for Queries - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Automatic SPARQL Benchmark Generation using FEASIBLE - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LANCE: Piercing to the Heart of Instance Matching Tools - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

LANCE: A Generic Benchmark Generator for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Enhancing Dataset Quality using Keys - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Interlinking: Performance Assessment of User Evaluation vs. Supervised Learning Approaches - M. Hassan, Mofeed; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Linked Data on the Web, LDOW 2015, co-located with the 24th International World Wide Web Conference {(WWW} 2015), Florence, Italy, May 19th, 2015)